Effect of a Terminated PVCap on Methane Gas Hydrate Formation - Zhiguang Song; Shiyuan Cui; Cuiping Tang; Yong Chen; Deqing Liang; Sibo Wang (Journal of Marine Science and Engineering, 2023)
Polyvinylcaprolactam (PVCap) is an economic kinetic inhibitor for hydrate formation in pipelines during oil and gas transportation. However, its application is limited because of the low inhibition performance under certain conditions. In this work, a modified PVCap on its chain end is proposed. 2-amino-3-propionic acid mercapto-terminated polyvinyl caprolactam (PVCap-NH <semantics>2</semantics> -COOH) was synthesized and its performance as a KHI for methane hydrate formation was evaluated under different conditions. Results showed that the performance of PVCap-NH <semantics>2</semantics> -COOH as a KHI was better than that of PVCap at the same concentrations. Gas hydrate samples with 1 wt.% PVCap-NH <semantics>2</semantics> -COOH were measured using Raman spectroscopy, XRD, and cryo-SEM. PVCap-NH <semantics>2</semantics> -COOH had a selective action on a specific crystal surface of the hydrates and could prevent methane molecules from entering large cages. Its inhibition ability increased with the decrease in the occupancy rate of large cages. The morphology of the gas hydrate crystal changed from porous in a pure water system to a chaotic but compact structure state in the system with PVCap-NH <math xmlns="http://www.w3.org/1998/Math/MathML" ...